Literatur Review Kolaborasi Manajemen Stratejik dengan Ilmu Ekonomi - Heri Fathurahman; B. Yuliarto Nugroho (Jurnal Siasat Bisnis, 2010)
The aim of this paper is to examine collaboration between strategic management and economics. These views are intended to challenge both economics and strategists to recognize each others contributions, limitations as well as the opportunities each faces in connecting theory and application. The importance of economic relationships for strategy is a central theme of this paper. Most of important literatures on strategy in the past 20 years are based on well-developed ideas from economics. Understanding robust economic relationships can help us understand why some strategies are well-suited to one set of conditions but not to other. The judicious application of economic principles to a firm’s circumstances can increase the odds of formulating and executing a successful business strategy. There is much to be said for viewing strategy from the perspective of multiple disciplines lenses. But depth of strategic knowledge is as important as breadth. Deep knowledge of any discipline permits the formulation of subtle and powerful hypotheses and development of rich strategies. An advance economics use for analyzing individual and institutional decision making is that it requires the analyst to be explicit about the key elements of the process of strategy. Keywords:    strategic management, economics, boundaries of the firm, market and competitive analysis, position and dynamics